THE ROLE AND VALUE OF MRI IN DIFFERENT VARIANTS OF DURA MATER SINUS STRUCTURE (Conferencea, 2022)
The role of venous circulation disorder in the origin and course of cerebral vascular diseases has long been underestimated. This can be explained by the previous difficulties of intravital assessment of cerebral venous hemodynamics using traditional methods of cerebral venous blood flow registration as well as by insufficient attention of researchers to this section of angiology.